Progressive Digitalization of Public Agencies - Sharanya, S; Shwetha, L; S, S Swarna; Varsha, AS; Patil, Veerseh (International Journal of Computer Sciences and Engineering, 2025)
Big data could be a potential instrument to vary standard association into perceptive association. There are a long discourse and visit on the usage of big data for the distinction in customary open relationship to present day and fast open relationship within the academician, experts, and policymakers. This examination hopes to analyze the sensibility and significance of large data for sharp association of open work environments. Creating layout demonstrates that numerous models have been created to clear up sharp association however correct analysis on the reputability and significance of monumental information for perceptive association of open affiliations is 'in the not too distant past lacking. This article fights that the usage of big data for marvelous association within the comprehensive network division will expand the capability of the general open affiliations fastest open association transport, pushing ahead straightforwardness, decreasing open issue and serving to the change into a pointy affiliation. This paper to boot battles that execution of large data for good association contains a essential add lucky, goof free, real and cost effective advantage development to subjects that prompts the practical money connected distinction during a nation. We applied ECC algorithm for security purpose to prevent the data.